DEVELOPING DIGITAL LITERACY OF LEARNING MEDIA INNOVATION BASED ON LOCAL WISDOM FOR ONLINE CLASS TO IMPROVE LISTENING AND WRITING SKILLS - Wayan Astu Werdistira (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Learning a new language is considered a difficult task because it needs more exercise in various skills. Media plays the important role in increasing the learners’ desire to learn by creating an atmosphere of fun. In this digital era, learning models utilize technology as learning media to provide wider access and opportunities for students in building their own knowledge. The availability of technology in education enables educators to plan and implement innovative and interactive learning models. This research is development research (R&D) which aims to develop the current media for teaching and learning the language in the digital era based on local wisdom for an online class to improve listening and writing skills in the information systems education program at ITB STIKOM Bali. Data was collected by means of documentation, interviews, observations, and questionnaires. The data collected was analyzed quantitatively to determine the average score, where the average score was categorized based on the evaluation table of reference criteria and qualitatively as a description of the score results obtained. The research procedure followed Luther’s model design proposed by Branch (2009) with some modifications. The steps were analyzing the students’ needs and curriculum analysis, designing the blueprint, and developing the first draft of the digital-based listening materials. This research developed digital literacy-based listening and writing materials based on the results of the needs analysis. The data from the needs analysis was analyzed quantitatively that obtained from the experts' judgment were analyzed through descriptive statistics. The digital literacy-based listening and writing materials were appropriate to be implemented as the listening and writing materials that could support the teaching and learning process for the Information Systems education program at ITB STIKOM Bali. This was supported by the result of the experts’ judgment who evaluate the appropriateness of the product in terms of content, language, presentation, and media aspect. The mean score in the experts’ judgment based on the materials evaluation in the aspect of content, language, and presentation was 3,8 which belonged to the very good category. The mean score based on the graphic evaluation was 3,8 which belonged to the very good category. This digital literacy-based listening and writing materials were packed into Google Form that consisted of 3 materials such as Word Processing, Asking and giving for information, and Globalization. Therefore, the written materials of the second draft and the final product of the digital-based listening materials are the same product.